Synthetic antibody-derived immunopeptide provides neuroprotection in glaucoma through molecular interaction with retinal protein histone H3.1 - Fomo, Kristian Nzogang; Schmelter, Carsten; Atta, Joshua; Beutgen, Vanessa M.; Schwarz, Rebecca; Perumal, Natarajan; Govind, Gokul; Speck, Thomas; Pfeiffer, Norbert; Grus, Franz H. (Frontiers in Medicine, 2022)
Glaucoma is a group of optic neuropathies characterized by the progressive degeneration of retinal ganglion cells (RGCs) as well as their axons leading to irreversible loss of sight. Medical management of the intraocular pressure (IOP) still represents the gold standard in glaucoma therapy, which only manages a single risk factor and does not directly address the neurodegenerative component of this eye disease. Recently, our group showed that antibody derived immunopeptides (encoding complementarity-determining regions, CDRs) provide attractive glaucoma medication candidates and directly interfere its pathogenic mechanisms by different modes of action. In accordance with these findings, the present study showed the synthetic CDR2 peptide (INSDGSSTSYADSVK) significantly increased the RGCs viability in vitro in a concentration-dependent manner (p < 0.05 using a CDR2 concentration of 50 µg/mL). Employing state-of the-art immunoprecipitation experiments, we confirmed that synthetic CDR2 exhibited a high affinity towards the retinal target protein histone H3.1 (HIST1H3A) (p < 0.001 and log2 fold change > 3). Furthermore, molecular dynamics (MD) simulations along with virtual docking analyses predicted potential CDR2-specific binding regions of HIST1H3A, which might represent essential PTM sites for epigenetic regulations. Quantitative MS analysis revealed that 39 proteins were significantly changed between CDR2-treated and untreated control retinae (p < 0.05). An up-regulation of proteins involved in the energy production (e.g., ATP5F1B and MT-CO2) as well as the regulatory ubiquitin proteasome system (e.g., PSMC5) was induced by the synthetic CDR2 peptide. On the other hand, metabolic key enzymes (e.g., DDAH1 and MAOB) as well as ER stress-related proteins (e.g., SEC22B and VCP) were identified as low abundant markers in CDR2-treated retinae and were also partially confirmed by microarray technology. Based on these findings, it can be hypothesized that the specific protein-peptide interaction influences the regulatory epigenetic function of HIST1H3A promoting the neuroprotective mechanism on RGCs in vitro. It also might serve as basis for a synergistic immunotherapy of glaucoma in the future.